Smorgasbord or symphony? Assessing public health nutrition policies across 30 European countries using a novel framework - Lloyd-Williams, F; Bromley, H; Orton, L; Hawkes, C; Taylor-Robinson, D; O'Flaherty, M; McGill, R; Anwar, E; Hyseni, L; Moonan, M; Rayner, M; Capewell, S (BioMed Central, 2014)
Background: Countries across Europe have introduced a wide variety of policies to improve nutrition. However, the sheer diversity of interventions represents a potentially bewildering smorgasbord. We aimed to map existing public health nutrition policies, and examine their perceived effectiveness, in order to inform future evidence-based diet strategies. Methods: We created a public health nutrition policy database for 30 European countries . National nutrition policies were classified and assigned using the marketing "4Ps" approach Product (reformulation, elimination, new healthier products); Price (taxes, subsidies); Promotion (advertising, food labelling, health education) and Place (schools, workplaces, etc.). We interviewed 71 senior policy-makers, public health nutrition policy experts and academics from 14 of the 30 countries, eliciting their views on diverse current and possible nutrition strategies. Results: Product Voluntary reformulation of foods is widespread but has variable and often modest impact. Twelve countries regulate maximum salt content in specific foods. Denmark, Austria, Iceland and Switzerland have effective trans fats bans. Price EU School Fruit Scheme subsidies are almost universal, but with variable implementation. Taxes are uncommon. However, Finland, France, Hungary and Latvia have implemented ‘sugar taxes’ on sugary foods and sugar-sweetened beverages. Finland, Hungary and Portugal also tax salty products. Promotion Dialogue, recommendations, nutrition guidelines, labelling, information and education campaigns are widespread. Restrictions on marketing to children are widespread but mostly voluntary. Place Interventions reducing the availability of unhealthy foods were most commonly found in schools and workplace canteens. Interviewees generally considered mandatory reformulation more effective than voluntary, and regulation and fiscal interventions much more effective than information strategies, but also politically more challenging. Conclusions: Public health nutrition policies in Europe appear diverse, dynamic, complex and bewildering. The "4Ps" framework potentially offers a structured and comprehensive categorisation. Encouragingly, the majority of European countries are engaged in activities intended to increase consumption of healthy food and decrease the intake of "junk" food and sugary drinks. Leading countries include Finland, Norway, Iceland, Denmark, Hungary, Portugal and perhaps the UK. However, all countries fall short of optimal activities. More needs to be done across Europe to implement the most potentially powerful fiscal and regulatory nutrition policies.